Betsy Baker! or, Too Attentive by Half; A Farce, in One Act - Morton, John Maddison, 1811-1891 (Salt Lake City, UT : Project Gutenberg, 2021)
"Betsy Baker! or, Too Attentive by Half; A Farce, in One Act" by John Maddison Morton is a comedic play written in the mid-19th century. The work falls under the category of farce, a theatrical genre characterized by exaggerated and improbable situations. Through its lighthearted and humorous nature, the play explores themes of love, jealousy, and the complexities of marital relationships, particularly focusing on the dynamics between husbands and wives. The plot revolves around Mr. Marmaduke Mouser, who is overly attentive to his wife, Mrs. Anastasia Mouser, to the point of suffocation. Their cousin, Mr. Crummy, realizes that this excessive affection is causing distress to Mrs. Mouser and devises a scheme to ignite her jealousy by suggesting that Mr. Mouser should fall in love with the laundress, Betsy Baker. As the farce unfolds, misunderstandings ensue, leading to a comical chase involving multiple characters. Meanwhile, Betsy becomes entangled in the plot, but as the comedy progresses, she asserts her own desires, ultimately revealing the absurdity of Crummy's plan. The play concludes with a humorous resolution that highlights the importance of balance in relationships and ends in a light-hearted manner as characters come together to celebrate their newfound understanding. (This is an automatically generated summary.)
Release date is 2021-03-11
Paul Haxo from scanned images graciously made available by the University of Michigan, the Hathi Digital Library, the Internet Archive, and the University of Warwick.
Keywords: English drama (Comedy); Women -- Drama; Farces